Illusory Speed is Retained in Memory during Invisible Motion. (May 2013) - Battaglini, Luca; Campana, Gianluca; Casco, Clara
The brain can retain speed information in early visual short-term memory in an astonishingly precise manner. We investigated whether this (early) visual memory system is active during the extrapolation of occluded motion and whether it reflects speed misperception due to contrast and size. Experiments 1A and 2A showed that reducing target contrast or increasing its size led to an illusory speed underestimation. Experiments 1B, 2B, and 3 showed that this illusory phenomenon is reflected in the memory of speed during occluded motion, independent of the range of visible speeds, of the length of the visible trajectory or the invisible trajectory, and of the type of task. These results suggest that illusory speed is retained in memory during invisible motion.